Short message service reduces dropout in childhood obesity treatment: a randomized controlled trial - De Niet, Judith; Bauer, Stephanie; Kordy, Hans (Health psychology, 2012)
Objective: Lifestyle programs can reduce the level of overweight in children; however, maintenance results and adherence to treatment are difficult to achieve. New technologies, such as the Short Message Service (SMS), might be a promising tool for enhancing interventions. The effect of an SMS approach aimed at improving treatment results and reducing dropout rates in a pediatric lifestyle intervention, is explored. Method: Overweight and obese children (N = 141; age 7-12 years) participating in a lifestyle program were randomly assigned to an intervention group receiving an SMS Maintenance Treatment (SMSMT) for 38 weeks (n = 73) or to a control group receiving no SMSMT (n = 68). Children were asked to send weekly self-monitoring data on exercise, eating behavior, and emotional well-being. In return, they received tailored feedback messages. A differential decrease in BMI was analyzed with repeated measures ANOVA and dropout with logistic regression analysis. Results: We found no significant difference in BMI decrease between the two groups after 12 months; however, we showed that the SMSMT group had 3.25 times less probability of dropping out after 1 year (p = .01) than controls. In the first 3 months of SMSMT, the SMSMT completers sent 0.80 SMSs per week, which reduced to 0.50 SMSs in the final 3 months. Younger children sent more SMSs (p = .03). Conclusions: These results indicate that SMSMT is effective in reducing dropout rates from a pediatric lifestyle intervention. Future research should examine the effectiveness of SMSMT on weight management and related psychosocial variables. (PsycINFO Database Record (c) 2016 APA, all rights reserved)